EVALUATION OF COLOR TRAPS FOR THE MANGO ATAULFO THRIPS IN THE SOCONUSCO, CHIAPAS - Virgen Sánchez Armando; Hernández Antonio Santiesteban; Cruz-López Leopoldo (Revista Mexicana de Ciencias Agrícolas, 2018)
In this paper colored traps were evaluated to capture thrips in mango cv. Ataulfo trees in Soconusco, Chiapas, Mexico. Sticky traps were compared in different colors: blue, yellow and violet. It was placed a trap of each color per tree and they were evaluated in five trees. The results showed that significantly more thrips were caught in violet traps.